2007
DOI: 10.1038/sj.ejcn.1602886
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil supplementation improves large arterial elasticity in overweight hypertensive patients

Abstract: Objectives: To observe the effect of fish oil supplementation on arterial elasticity and blood pressure (BP) in overweight hypertensive patients. Subjects and methods: This was a double-blind, randomized and placebo-controlled clinical study, in which 52 overweight hypertensive patients from a community were selected and randomly allocated to two groups (26 in the fish oil group (3 g day À1 , fish oil capsules) and 26 in the placebo group (only capsules). All the subjects were follow-up for 8 weeks. The arteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 27 publications
2
36
0
1
Order By: Relevance
“…A summary of the International Study of Macro/Micronutrients and Blood Pressure (INTERMAP) reported that total PUFA, linoleic acid (LA), total n-3 FA, and α-linolenic acid (ALA), were inversely associated with BP (10). Data from meta-analyses (11,12) and clinical trials (13,14) have indicated that n-3 PUFA supplementation dose-dependently reduces BP in hypertensive patients, but not in normotensive individuals. A large-scale, population-based INTERMAP indicated that dietary intake of n-3 PUFA was inversely associated with BP levels in middle-aged normotensive individuals (15).…”
Section: Introductionmentioning
confidence: 99%
“…A summary of the International Study of Macro/Micronutrients and Blood Pressure (INTERMAP) reported that total PUFA, linoleic acid (LA), total n-3 FA, and α-linolenic acid (ALA), were inversely associated with BP (10). Data from meta-analyses (11,12) and clinical trials (13,14) have indicated that n-3 PUFA supplementation dose-dependently reduces BP in hypertensive patients, but not in normotensive individuals. A large-scale, population-based INTERMAP indicated that dietary intake of n-3 PUFA was inversely associated with BP levels in middle-aged normotensive individuals (15).…”
Section: Introductionmentioning
confidence: 99%
“…Although the underlying mechanisms remain to be elucidated, the rapidity with which oral doses of SLO improve vascular structures and/or functions indicates a direct effect on the physiological components rather than the structural components that regulate the elasticity of the arterial wall, as was observed for vitamin E (34), as well as for fish oil (35,36) and n-3 long-chain fatty acids (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Based on secular trends in the United States and the United Kingdom, the greater reduction in stroke mortality from 1990 through 2002 in the U.S. have been tentatively attributed to the introduction of folic acid fortification [8]. A previous meta-analysis of published results from some of the folic acid trials, reported that folic acid could reduce the risk of stroke [9]. Under normal metabolic circumstances, there is a strict balance between Hcy formation and elimination.…”
Section: Homocysteine and Risk Of Cvdmentioning
confidence: 99%